PENGEMBANGAN POTENSI DESA MELALUI PEMBANGUNAN KAMPUNG DIGITAL BERBASIS LITERASI - Welly Nores Kartadireja; Iis Lisnawati; Ai Siti Nurjamilah; Fikri Hakim (KARISMAS - JURNAL PENGABDIAN KARYA INOVASI MASYARAKAT, 2025)
The "digital village" program is a program promoted by the government to equalize the level of digital literacy in remote villages. The digital village program is expected to optimize village potential in various lines and aspects of life. The village revealed that the main obstacle in establishing a digital village was related to the literacy level of the village community. To be able to optimize all the potential that exists through the digital village program, a well-literate community is needed. This is one of the obstacles with a high level of urgency according to the village. Based on the results of observations, the service team plans to carry out further service in Tawangbanteng Village by taking the main issue, "Development of Village Potential through Building a Digital Village Based on 2 Literacy". The method that will be implemented in this PbM-PKM activity is gradual guidance consisting of the planning stage, namely coordinating with relevant partners, in this case the Head of Tawangbanteng Village, Kec. Sukaratu District. Tasikmalaya and the Head of the Al Hikmah Islamic Boarding School; Identify potential problems with a high level of urgency; Formulate the flow and technical implementation. The implementation stage is the implementation of seminars/workshops related to the relevance of literacy, digitalization and the concept of digital literacy, workshops related to optimizing information technology based on facilities and facilities already owned by the village as well as handing over an inventory of supporting facilities for activities, implementing skills (obtained from seminars and workshops) and optimizing hardware (supporting facilities and equipment) in activities that support the implementation of the "digital village" program. The evaluation phase is carried out together with partners to identify the level of achievement of the activities that have been carried out. Achievement indicators are prepared at the beginning together with reference to the digital village program targets launched by the government as well as the provision of material assistance deemed necessary to be able to resolve all complaints and problems by obtaining information through the implementation of this PbM-PKM.